HIERARCHICAL TWO-WAY SENSITIVITY ANALYSIS IN DIVERSE BENEFIT SCENARIO OF MATENGGENG DAM FEASIBILITY - Roy, Andreas F. V.; Yonathan, Tan Leonardo (LPPM Universitas Negeri Jakarta, 2024)
The Indonesian government formulated plans for the construction of the Matenggeng Dam, aiming to enhance local agricultural productivity. This dam will store water from the Cijolang River, a tributary of the Citanduy River. The construction of Matenggeng Dam encompasses option of municipal water enhancement and four normal water levels: 190m, 194m, 197m, and 199m. According to the hydrology, social-economic, and dam structure design reports, each option entails distinct benefits and costs. The report informed dam’s agriculture potential benefit, land use, and cost by each water level option. To assess the project's viability, an economic analysis and hierarchical two-way sensitivity analysis has been conducted to examine the impact of water level variations on the economic evaluation outcomes. Results obtained at a discount rate of 10.08% indicate that 194m and 197m water level options exhibit positive NPV, IRR greater than the interest rate, PBP less than 50 years, and a BCR exceeding 1. While both options demonstrate feasibility, the 194m appears more favorable. Despite the 197m water level presenting a slightly higher IRR by 0.02%, respectively, it incurs a cost deviation of IDR 100 billion. However, the 194m water level emerges as a more enticing choice due to its lower cost implications.